2020
DOI: 10.1155/2020/7945309
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Dental Surgeon in Controlling the Dissemination of COVID-19: A Literature Review

Abstract: As early as December 2019 in the province of Hubei, China, contamination of patients with pneumonia of an unknown etiology occurred. These patients presented with symptoms such as coughing, sore throat, malaise, diarrhea, high fever, and dyspnea. This emerging disease was named COVID-19 due to being part of the group of coronaviruses (CoVs) belonging to the subfamily Orthocoronavirinae, in the Coronaviridae family and in the Nidovirales order. COVID-19 is most commonly transmitted through speech, coughing, sne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
0
4
0
9
Order By: Relevance
“…Following the exclusion of one duplicate article, the abstracts of the remaining 74 articles were screened, with 66 articles excluded for not meeting the inclusion criteria. Finally, eight articles were identified as eligible after full-text screening [2][3][4][5][6][7][8][9]. These eight articles are listed in Table 1, along with a summary of their key points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the exclusion of one duplicate article, the abstracts of the remaining 74 articles were screened, with 66 articles excluded for not meeting the inclusion criteria. Finally, eight articles were identified as eligible after full-text screening [2][3][4][5][6][7][8][9]. These eight articles are listed in Table 1, along with a summary of their key points.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate personal protective equipment (PPE) is important in the clinical practice of corona vortices. Standard PPE provides the same protection as the surgical mask, eye shield, gown, and gloves in Bastia et al [2] This article aimed to inform dental professionals about the COVID-19 pandemic and to present the implication of the virus. It suggested that dental professionals are at high risk for contacting COVID-19 because they are exposed to droplet infection through saliva.…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
“…7 Hastalığın yayılmasında oral sekresyonların rolü hakkında daha detaylı çalışmalar gerekse de dental işlemler sırasında kan ve tükürükle karışık büyük miktarda aerosol açığa çıktığından hekim ve yardımcı personelin koruyucu önlemler alması gerekmektedir. 37 Airatörler ve ultrasonik cihazlar yüksek miktarda aerosol oluşturduğundan kimyasal çürük temizleme yöntemleri ve el aletleri kullanılmalı, bistüri kotere tercih edilmeli, rezorbe olan süturlar kullanılmalıdır. 38…”
Section: Sonuçunclassified
“…Furthermore, COVID-19 transmission through droplets can occur when the distance between two people is less than 1 m apart. Dental care workers are vulnerable to cross-transmission of COVID-19 due to long treatment durations and the short (less than 1 m) distance between the practitioner and the patient 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Dental personnel risk occupational exposure to SARS-COV-2 infection due to contact with the patient's mouth, body fluids, and airborne pathogens 30) . In addition, the significant amount of aerosol produced during dental procedures also contributes to the risk of COVID-19 infection 9) . It is important for dental personnel to have appropriate PPE, including gowns, gloves, protective glasses, and masks; masks in particular provide a very important protective barrier 33) .…”
mentioning
confidence: 99%